Entrepreneurs’ self-perception of skills in rural tourism - Castro, Conceição (2019)
The objective of this paper is to study the perception of entrepreneurial and personal maturity skills among owners of rural tourism businesses and structure these skills. The main obstacles to entrepreneurship felt by these entrepreneurs are also analysed. Using the results of a survey of rural tourism businesses in Northern Portugal, exploratory (EFA) and confirmatory factor analysis (CFA) were conducted. The data was evaluated through CFA, using Analysis of Moment Structure and performed a Structural Equation Model. The CFA led to two distinct factors: one includes emotional coping, critical evaluation and networking (personal maturity) skills, while the other (entrepreneurial) includes goal setting and environment scanning skills. The findings reveal, after a cluster analysis based on the resulting component scores, three different groups of entrepreneurs with different perception of competencies, background and type of business. The owners/managers encountered some restrictions in the start-up process as the bureaucracy and the lack of financial support and information. Studying rural tourism owner's perceived entrepreneurial competencies provide advances in identifying its dimensionality and corresponding profiles and help defining strategies to enhance them, in order to promote success and local development.